Lumbar spondylolysis without spondylolisthesis: recognition of isolated posterior element subluxation on sagittal MR. - Ulmer, J L; Mathews, V P; Elster, A D; King, J C (American Journal of Neuroradiology, 1995)
PURPOSE To document the occurrence of isolated dorsal subluxation of posterior elements in cases of lumbar spondylolysis without spondylolisthesis both quantitatively (using spinal canal measurements) and qualitatively (by visual inspection) on sagittal MR images. METHODS Retrospective analysis identified 63 patients with lumbar spondylolysis (confirmed by CT or conventional radiography) who had undergone MR imaging. From these we identified 12 patients with pars interarticularis defects but no evidence of spondylolisthesis. Measurements of anteroposterior spinal canal diameters were performed in these 12 patients to ascertain whether the sagittal canal diameter at the level of the spondylolysis exceeded the normal range as determined from 100 control subjects. RESULTS In 9 of 12 patients the spinal canal was abnormally widened at the level of the spondylolysis because of dorsal subluxation of posterior elements. In 5 of these patients, the subluxation was readily visible on midline sagittal MR images. In 4 patients, spinal canal measurements were necessary to document this phenomenon. CONCLUSION In the majority of patients with spondylolysis but without spondylolisthesis, sagittal MR images can show isolated dorsal subluxation of posterior spinal elements.